Phosphate fertilization improves vegetative growth and quality of pine cone seedlings - Carvalho, Jullyanna Nair de; Carvalho, Júnia Naara da Silva; Carvalho, Pollyanna Aparecida de; Basílio, Letícia Silva Pereira [UNESP]; Lima, Augusto Miguel Nascimento; Pio, Rafael (Lepidus Tecnologia, 2022)
Adding phosphorus in the composition of the substrate for the seedlings production contributes to a faster growth of seedlings, increases the resistance to biotic and abiotic stresses, also improves the efficiency in the use of nutrients and water in many vegetal species. The goal of this research was to evaluate the effect of levels of simple superphosphate on the production of pine cone (Annona squamosa L.) seedlings. Six doses of single superphosphate (0.0 kg m-3; 0.75 kg m-3; 1.5 kg m-3; 2.25 kg m-3, 3.0 kg m-3 e 3.75 kg m-3 of substratum) were tested. A completely randomized design was used, with four replications and ten plants per plot. At 120 days after sowing, number of leaves, leaf area, shoot height, stem diameter, shoot dry mass, root dry mass, total dry mass, ratio between shoot dry mass and root dry mass, chlorophyll a, chlorophyll b, total chlorophyll, and Dickson’s Quality Index were evaluated. More vigorous pine cone seedlings, with maximum growth, were noted with the single superphosphate application between 0.6 to 1.2 kg m-3 of substrate. The phosphate fertilizer favored the growth especially of the roots and leaf area and improved the quality of pine cone seedlings.
Keywords: Annona squamosa; seedlings production; simple superphosphate